Brain Embolism Secondary to Cardiac Myxoma in Fifteen Chinese Patients. (9th March 2014) - Long, Youming; Gao, Cong
Abstract : Background . Heart myxoma-related embolisms commonly involve the central nervous system, but data are lacking in Chinese patients. Methods . 27 patients diagnosed with myxoma were reviewed retrospectively. Results . Among 27 patients, fourteen (51.9%) patients were women. Fifteen (55.6%) patients had brain embolisms. Rarely, patients were misdiagnosed with central nervous system vasculitis ( n = 2), moyamoya disease ( n = 1), and neuromyelitis optica ( n = 1). We found positive associations between mRS (>3) and female gender ( r = 0.873, P < 0.0001 ), infection ( r = 0.722, P = 0.002), severe complications ( r = 0.722, P = 0.002), systolic blood pressure (SBP) of <120 mmHg ( r = 0.6, P = 0.018), WBC count of >10 × 10 9 /L ( r = 0.722, P = 0.002), tumour size ( r = 0.866, P < 0.0001 ), bilateral brain lesions ( r = 0.60, P = 0.018), and total anterior circulation infarction (TACI) ( r = 0.667, P = 0.007). The independent relationships among these factors and outcomes could not be confirmed (P > 0.05 ). Conclusions . Neurologic manifestations in Chinese patients with cardiac myxoma-related stroke were complicated and multifarious. Female gender, infection, other severe complications, low SBP, tumour size, bilateral brain lesions, TACI, and high WBC counts could be associated with a poor prognosis.